The frozen-thawed sperm protein of Indonesian Toraya buffaloes is significantly associated with sperm kinematics, acrosome integrity, and mitochondrial membrane potential (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The study aimed to characterize frozen-thawed sperm proteins and their correlation with sperm kinematics, acrosome integrity, and mitochondrial membrane potential (MMP) in Indonesian Toraya buffalo bulls. Materials and Methods: Semen was obtained from six Toraya buffaloes classified as Saleko and Bonga 4–10 years old. The frozen semen was analyzed for sperm motility, sperm kinematics, viability, abnormalities, membrane integrity, intact acrosome, MMP, DNA integrity, and sperm protamine (PRM) deficiency. Sperm protein concentration (Prot. Con) was determined by the bicinchoninic acid, and protein molecular weight (MW) was determined using 1D sodium dodecyl sulfate-polyacrylamide gel electrophoresis with 4%–20% gradient gel and 6.5–240 kDa protein marker. Results: The results of this study showed that the quality of frozen semen from Toraya buffalo bulls is in a good category and suitable for use in artificial insemination programs. The sperm quality differed significantly (p < 0.05) between individuals, immunofluorescence examination of intact acrosome, PRM deficiency, intact MMP, and intact DNA showed no significant difference (p < 0.05). Pearson correlations in this study showed that sperm Prot. Con has a significant correlation (p < 0.05) with acrosome integrity. The sperm protein band (Prot. Band) correlated significantly (p < 0.05) with sperm kinematic parameters and intact MMP. The average sperm Prot. Con of Toraya buffalo was 77.29 ± 39.26 µg/ml and 4–13 Prot. Bands with 6–240 kDa of MW were detected, with Prot. Bands of 16, 50, 70, and 115 kDa having higher intensity. Conclusions: Frozen-thawed sperm protein is correlated with sperm kinematics, acrosome integrity, and MMP. The proteins were found to correlate with sperm quality and fertility in Toraya buffalo bulls.J. Adv. Vet. Anim. Res., 11(4): 869–879, December 2024http://doi.org/10.5455/javar.2024.k838